Study on the spatial variability of thermal landscape in Xi’an based on OSM road network and POI data - Wu, Jiang; Han, Shenshan; Shi, Leijie; Hui, Qun (Frontiers in Ecology and Evolution, 2023)
As the primary contributor to the urban heat island effect, the construction land can be used to understand the spatial variation characteristics of the thermal landscape within the city at the microscopic scale. Taking the main urban area of Xi'an as the study area, this paper divides the minimum urban land unit by using OpenStreetMap (OSM) road network data and employs the kernel density analysis method based on Point of interest (POI) data to construct seven types of urban functional blocks. Furthermore, this paper also establishes a thermal landscape footprint characterization model to investigate the impact range of thermal landscape footprint for various types of functional blocks and quantitatively evaluate the spatial variation characteristics of urban thermal landscape, which is of great significance to the enhancement of urban ecological environment. The study indicates that: (1) The spatial distribution of urban functional blocks presents highly coupled characteristics with POI kernel density. (2) The surface thermal landscapes of seven types of urban functional blocks are predominantly medium-temperature and sub-high-temperature pixels, with the mean values of thermal fields ranked as logistics and storage blocks > industrial development blocks > transportation hub blocks > comprehensive service blocks > residential and living blocks > commercial and business blocks > strategic reserved blocks. (3) Apart from the strategic reserved blocks, the remaining urban functional blocks can produce thermal diffusion phenomena to the surrounding areas, and their thermal landscape footprints are obviously differentiated, with their influence ranges ranked as industrial development blocks > logistics and storage blocks > comprehensive service blocks > residential and living blocks > commercial and business blocks > transportation hub blocks. The findings of the study can provide scientific guidance for both the enhancement of urban ecological environment as well as the rational planning and layout of the city.